HUBUNGAN UMUR DAN IMT TERHADAP KEJADIAN HIPERTENSI PADA BURUH ANGKUT - Agustin, Sefentina; Alza, Yessi; Lestari, Dwi; Lellu, Amos; Wahyurianto, Yasin (Ensiklopedia of Journal, 2024)
Abstract: Increased blood pressure that lasts for a long time can cause damage to the kidneys (kidney failure), heart (coronary heart disease) and brain (causing stroke) if not detected early and received adequate treatment. Based on preliminary data obtained from the Lima Puluh Kota Health Center which is right in the area where the workers live, it shows that high blood pressure or hypertension is one of the diseases with the highest rate for the last 3 months, from December 2022 to February 2023. The purpose of the study was to determine the correlation of age and imt to the incidence of hypertension in transport workers. This type of research is quantitative using a cross sectional design. This research was conducted on workers, especially transport workers at Sungai Duku Port, with a total sample of 133 transport workers. The instrument used was a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between IMt to the incidence of hypertension (p value: 0.012) and there was no relationship between age to the incidence of hypertension (p value: 0.611). It is recommended for respondents to maintain a diet and routine physical activity and avoid stress.Keywords: Transport Workers, BMI, Hypertension, Age